THE ROLE OF RELIGIOUS EDUCATION IN SHAPING THE CHARACTER OF THE YOUNGER GENERATION IN THE DIGITAL AGE - Sahruddin Sahruddin (International Journal of Teaching and Learning, 2025)
The digital era has had a significant impact on the mindset, behaviour and lifestyle of the younger generation. These changes require education that is not only knowledge-oriented, but also focuses on building strong character. Religious education has a strategic role in instilling moral, ethical and spiritual values, which are the main foundations for facing the challenges of globalisation and the rapid flow of information. This study aims to analyse the role of religious education in shaping the character of the younger generation in the digital age, focusing on the internalisation of religious values, relevant learning methods, and the use of technology as an educational medium. The research method used is a literature study with a descriptive qualitative approach, examining various literature related to religious education, technological developments, and character building. The results of the study show that religious education is effective in strengthening the values of integrity, responsibility, tolerance, and social awareness when supported by innovative learning methods and the wise use of digital technology. In conclusion, religious education plays an important role as a moral fortress for the younger generation, as well as a guideline in building noble character amid the challenges and opportunities of the digital age.